Village records of Chelsworth, Suffolk, 1441-1904 - Quinlan, Bernard (UK Data Service, 2004)
This dataset is derived from a collection of published and unpublished information collected in preparation for a history of the village of Chelsworth, Suffolk. The data deposited at History Data Service contained information concerning named individuals living in Chelsworth up to the present day. Although this data has been preserved, for data protection reasons it is not available to users. This data will be released as and when it is appropriate in the future.